2012
DOI: 10.4236/ojpm.2012.23051
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and foetal risk factors of cerebral palsy among Iraqi children. A case control study

Abstract: Background: The importance of studying cerebral palsy comes from the fact that, this disorder imposes huge burden families psychologically, emotionally, financially and socially. Moreover, it imposes a major burden on the National Health System because it is simply a chronic disorder, which needs a continuous care and multiple financial resources. At the same time, it needs collaborative efforts and team work between many parties and organizations for a good management and rehabilitation. In Iraq, risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…4,6 In our study pregnancy induced hypertension amounts to 9% which is higher than that of a study done by Gowda et al, Pattar et al study, Saadi et al 6,7,12 Gestational diabetes is seen in 7% of mothers in our which was similar to that found in to that seen in Saadi et al 7 Among the probable etiologic factors in the present study, perinatal factors were the most prevalent. However in a few cases, more than one probable cause was taken into account, as it was difficult to pin point one etiological agent.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…4,6 In our study pregnancy induced hypertension amounts to 9% which is higher than that of a study done by Gowda et al, Pattar et al study, Saadi et al 6,7,12 Gestational diabetes is seen in 7% of mothers in our which was similar to that found in to that seen in Saadi et al 7 Among the probable etiologic factors in the present study, perinatal factors were the most prevalent. However in a few cases, more than one probable cause was taken into account, as it was difficult to pin point one etiological agent.…”
Section: Discussionsupporting
confidence: 78%
“…[3][4][5] In our study consanguinity amounts to 38% which is similar to that found in the study done by Gowda et al and Saadi et al which was comparable with few Turkish studies who have noted a high number of marriages between relatives (21% of all marriages). [6][7][8][9] The increased frequency of consanguinity among parents of children with CP, and the strong association with a positive family history suggests the role of genetic factors in the pathogenesis of CP in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 In addition to the multifactorial clinical aspects, the causes of CP can also be related to healthcare management and quality. 6 A systematic review reported a prevalence of 2.11 per 1,000 live births. 7 The low prevalence of CP makes it difficult to identify risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…8 Most of the epidemiological studies on CP were conducted in developed countries, 4,7,9,10 despite efforts by researchers from various developing countries. 6,[11][12][13][14][15][16] An increased risk of cerebral palsy in low-and middle-income countries, due to exposure to perinatal events, has been suggested. 2,17 The epidemiological aspects of CP need further clarification, especially in socioeconomic contexts characterized by social inequities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation